Analisis Reduplikasi Dalam Cerpen Menunggu Karya L Maranggi - Rahayu, Aprilia Retnoning; Nurfatonah, Endang; Hasanah, Uswatun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Reduplication is a morphological process that involves repeating part or all of the basic form of a word to create a new meaning or give a certain effect. This study discusses reduplication in the short story Menunggu by L Malaranggi. This study is a type of qualitative research and uses a descriptive method. The techniques used in collecting data in this study are reading techniques and note-taking techniques. In this study, there are 13 data on the type of reduplication, 111 data on complete reduplication, 2 data on partial reduplication, and 6 data on affixed reduplication.